Centripetal forces in China's Economic Take-Off - Dayal-Gulati, Anuradha (IMF Working Papers; Working Paper, 2000)
This paper uses provincial time series data from China to empirically investigate two propositions relating to economic development: (i) that economic takeoff is associated with technological transfer through foreign direct investment (FDI); and (ii) that takeoff is accompanied, at least in the short term, by widening income inequality. The results indicate that FDI flows have increased the rate of convergence in per capita incomes across China's provinces. However, the pattern of FDI, which has gone mainly to the relatively wealthy provinces, has caused different provinces to converge to different steady states.